Radiographic Evaluation of Children with Febrile Urinary Tract Infection: Bottom-Up, Top-Down, or None of the Above? - Michaella M. Prasad; Earl Y. Cheng (Advances in Urology)
The proper algorithm for the radiographic evaluation of children with febrile urinary tract infection (FUTI) is hotly debated. Three studies are commonly administered: renal-bladder ultrasound (RUS), voiding cystourethrogram (VCUG), and dimercapto-succinic acid (DMSA) scan. However, the order in which these tests are obtained depends on the methodology followed: bottom-up or top-down. Each strategy carries advantages and disadvantages, and some groups now advocate even less of a workup (none of the above) due to the current controversies about treatment when abnormalities are diagnosed. New technology is available and still under investigation, but it may help to clarify the interplay between vesicoureteral reflux, renal scarring, and dysfunctional elimination in the future.